Buyer and Nonprofit Levers to Improve Supplier Environmental Performance. Issue 6 (21st October 2016) - Karaer, Özgen; Kraft, Tim; Khawam, John
Abstract : Material IQ (MiQ) is a new decision tool designed by GreenBlue to help suppliers safely share sensitive chemical‐toxicity data with their customers. As GreenBlue takes MiQ to market, it must determine under what market conditions to promote the use of MiQ and when to recommend that a buyer uses its implementation as an opportunity to work with an existing supplier. We study GreenBlue's problem in two parts. First, we investigate when a buyer can use a wholesale price premium and/or buyer–supplier cost sharing to improve a supplier's environmental performance. Based on our findings, we then develop insights into GreenBlue's strategy. We model both a single‐supplier and a supplier‐competition setting. We find that in the single‐supplier setting, if the buyer's optimal strategy is to offer the supplier a premium, then he also fully subsidizes her investment cost to build quality. By developing the supplier's capabilities, the buyer can increase the impact of the premium he offers. In the supplier‐competition setting, although cost sharing is less effective as a lever, cases can occur in which the buyer chooses to share costs and prevent the incumbent supplier from having to compete. From GreenBlue's perspective, promoting the use of MiQ and cost sharing are often viable strategies when there exists a one‐to‐one relationship between a buyer and a supplier. However, GreenBlue's strategy becomes more restricted when competition exists between suppliers. Only when the relative market awareness of quality is high and there is a dominant party in the supply chain should GreenBlue recommend the use of MiQ.